Contradictions and Challenges in Representing the Colonial Past: Herero Memory Activism in Namibia - Hana Horáková (Modern Africa, 2024)
This paper attempts to investigate recent urban space-making practices and imaginaries of two different civic actors: Swakopmund City Tour, operated by Namibian Germans depicting the history of Swakopmund linked to German heritage, and a group of Herero activists around Swakopmund Genocide Museum, challenging the monopoly in framing representations of urban heritage and history, and presenting alternative memory narratives. The aim is to explore how the official memory is dealt with in present day-remembrance policies and practices, and how it is challenged by alternative memory driven by Herero activists. Conceptually, the notion of a mnemoscape (Kössler, 2012) is used, including both intangible and tangible aspects of the remembrance of collective experience. Methodologically, the paper is largely based on the outcomes of a short fieldwork in the urban environment of Swakopmund in 2022.